해양구조용강의 피로크랙진전특성에 미치는 쇼트피닝 투사속도의 영향 - 박경동(KYOUNG-DONG PARK); 노영석(YOUNG-SOK NO) (Han-guk haeyang gonghak hoeji (Online), 2003)
The development of new materials with light weight and high strength has become vital to the machinery, aircraft and auto industries. However, there are a lot of problems with developing such materials that require such expensive tools, as well as a great deal of time and effort. Therefore, the improvement of fatigue life through, the adoption of residual stress, is the main focus. The compressive residual stress was imposed on the surface according to each shot velocity(1800, 2200, 2600, 3000rpm) based on Shot-peening, which is the method of improving fatigue life and strength. By using the methose mentioned above, we arrived at the following conclusions; 1. The fatigue crack growth rate(da/dN) of the Shot-peened material was lower than that of the Un-peened material. In stage I, $Δ$K$_{th}$, the threshold stress intensity factor, of the shot-peen processed material is high in critical parts, unlike the Un-peened material. Also m, fatigue crack growth exponent and number of cycle of the Shot-peened material was higher than of the Un-peened material. That is concluded from effect of da/dN. 2. Fatigue life shows more improvement in the Shot-peened material than in the Un-peened material. Compressive residual stress of the surface on the Shot-peen processed operate resistance force of fatigue crack propagation.